2022
DOI: 10.1177/00031348221101483
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Discharge Opioid Bundle in Adult Trauma Patients Decreases the Amount of Opioids Prescribed at Discharge

Abstract: Background Opioids remain the mainstay treatment of acute pain caused by trauma. The lack of evidence driven prescribing creates a challenging situation for providers. We hypothesized that the implementation of a trauma discharge opioid bundle (TDOB) would decrease the total morphine milligram equivalents (MME) prescribed at discharge while maintaining pain control. Methods This was a pre-post study of adult trauma patients before and after implementation of a TDOB to guide the prescription of opioids and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This project aimed to evaluate the impact of discharge care bundles on provider prescription rates of statins. One study showed how a discharge opioid bundle significantly decreased unnecessary opioid prescribing at discharge while increasing the use of nonopioid adjunct pain medications (Krebsbach et al, 2022). Vani et al (2022) found that BPAs in the EHR to alert providers to prescribe guideline-directed medical therapy on hospital discharge in atherosclerotic cardiovascular disease patients resulted in a 4.0% increase in statin use and a 3.1% in antithrombotic use.…”
Section: Goals Objectives and Expected Outcomesmentioning
confidence: 99%
“…This project aimed to evaluate the impact of discharge care bundles on provider prescription rates of statins. One study showed how a discharge opioid bundle significantly decreased unnecessary opioid prescribing at discharge while increasing the use of nonopioid adjunct pain medications (Krebsbach et al, 2022). Vani et al (2022) found that BPAs in the EHR to alert providers to prescribe guideline-directed medical therapy on hospital discharge in atherosclerotic cardiovascular disease patients resulted in a 4.0% increase in statin use and a 3.1% in antithrombotic use.…”
Section: Goals Objectives and Expected Outcomesmentioning
confidence: 99%